The Mechanism of Action of SAAP-148 Antimicrobial Peptide as Studied with NMR and Molecular Dynamics Simulations - Morgane Adélaïde; Evgeniy Salnikov; Francisco Ramos-Martín; Christopher Aisenbrey; Catherine Sarazin; Burkhard Bechinger; Nicola D’Amelio (Pharmaceutics, 2023)
Background: SAAP-148 is an antimicrobial peptide derived from LL-37. It exhibits excellent activity against drug-resistant bacteria and biofilms while resisting degradation in physiological conditions. Despite its optimal pharmacological properties, its mechanism of action at the molecular level has not been explored. Methods: The structural properties of SAAP-148 and its interaction with phospholipid membranes mimicking mammalian and bacterial cells were studied using liquid and solid-state NMR spectroscopy as well as molecular dynamics simulations. Results: SAAP-148 is partially structured in solution and stabilizes its helical conformation when interacting with DPC micelles. The orientation of the helix within the micelles was defined by paramagnetic relaxation enhancements and found similar to that obtained using solid-state NMR, where the tilt and pitch angles were determined based on 15N chemical shift in oriented models of bacterial membranes (POPE/POPG). Molecular dynamic simulations revealed that SAAP-148 approaches the bacterial membrane by forming salt bridges between lysine and arginine residues and lipid phosphate groups while interacting minimally with mammalian models containing POPC and cholesterol. Conclusions: SAAP-148 stabilizes its helical fold onto bacterial-like membranes, placing its helix axis almost perpendicular to the surface normal, thus probably acting by a carpet-like mechanism on the bacterial membrane rather than forming well-defined pores.